Investigation of DC-AC converter control techniques with enhanced MOSFET gate driver - Bouazza, Elmourabit; Jalil, Akaaboune; Mohamed, Oulaaross; Mohamed, Benchagra (International Journal of Applied Power Engineering (IJAPE), 2025)
To promote the use of photovoltaic (PV) systems and reduce costs, it is crucial to develop innovative approaches for grid integration, thereby contributing to global power generation. This article presents the development of an integrated power circuit using the TOSHIBA-TLP350 as a gate driver for the implementation of a single-phase H-bridge inverter, combined with inductor–capacitor–inductor (LCL) filters. This circuit was designed and controlled using a high-frequency pulse width modulation (PWM) signal generated by an ATmega328P microcontroller board, with a predefined program, to facilitate the filtration and reduction of both current and voltage harmonics present at the output of the filters. The study primarily focuses on a grid-connected mode of operation but also demonstrates adaptability to the islanded mode. The proposed application in this article can be adapted to other renewable energy conversion systems. The effectiveness of this achievement is demonstrated through detailed experimental results, highlighting the potential benefits for cost reduction and performance improvement of photovoltaic systems.